My Baby's Movements: a stepped‐wedge cluster‐randomised controlled trial of a fetal movement awareness intervention to reduce stillbirths. (24th October 2021) - Flenady, V; Gardener, G; Ellwood, D; Coory, M; Weller, M; Warrilow, KA; Middleton, PF; Wojcieszek, AM; Groom, KM; Boyle, FM; East, C; Lawford, HLS; et al.
Abstract : Objective: The My Baby's Movements (MBM) trial aimed to evaluate the impact on stillbirth rates of a multifaceted awareness package (the MBM intervention). Design: Stepped‐wedge cluster‐randomised controlled trial. Setting: Twenty‐seven maternity hospitals in Australia and New Zealand. Population: Women with a singleton pregnancy without major fetal anomaly at ≥28 weeks of gestation from August 2016 to May 2019. Methods: The MBM intervention was implemented at randomly assigned time points, with the sequential introduction of eight groups of between three and five hospitals at 4‐monthly intervals. Using generalised linear mixed models, the stillbirth rate was compared in the control and the intervention periods, adjusting for calendar time, study population characteristics and hospital effects. Main outcome measures: Stillbirth at ≥28 weeks of gestation. Results: There were 304 850 births with 290 105 births meeting the inclusion criteria: 150 053 in the control and 140 052 in the intervention periods. The stillbirth rate was lower (although not statistically significantly so) during the intervention compared with the control period (2.2/1000 versus 2.4/1000 births; aOR 1.18, 95% CI 0.93–1.50; P = 0.18). The decrease in stillbirth rate was greater across calendar time: 2.7/1000 in the first versus 2.0/1000 in the last 18 months. No increase in secondary outcomes, including obstetric intervention or adverse neonatal outcome, was evident. Conclusions: The MBM intervention did not reduce stillbirths beyond the downward trend over time. As a result of low uptake, the role of the intervention remains unclear, although the downward trend across time suggests some benefit in lowering the stillbirth rate. In this study setting, an awareness of the importance of fetal movements may have reached pregnant women and clinicians prior to the implementation of the intervention. Tweetable abstract: The My Baby's Movements intervention to raise awareness of decreased fetal movement did not significantly reduce stillbirth rates. Tweetable abstract: The My Baby's Movements intervention to raise awareness of decreased fetal movement did not significantly reduce stillbirth rates. Linked article This article is commented on by Alexander E. P. Heazell, p. 42 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16954 .